Role of glucocorticoid and mineralocorticoid receptors in rainbow trout (Oncorhynchus mykiss) skeletal muscle: A transcriptomic perspective of cortisol action - Aedo, Jorge E.; Zuloaga, Rodrigo; Aravena-Canales, Daniela; Molina, Alfredo; Valdés, Juan Antonio (Frontiers in Physiology, 2023)
Cortisol is an essential regulator of neuroendocrine stress responses in teleost. Cortisol performs its effects through the modulation of glucocorticoid receptor (GR) and mineralocorticoid receptor (MR), activating gene expression. Until now the contribution of both receptors in the global transcriptional response in teleost skeletal muscle has not been explored. To understand in a comprehensive and global manner how GR and MR modulates the skeletal muscle transcriptomic response, we performed RNA-seq analysis. Juvenile rainbow trout (Oncorhynchus mykiss) pretreated with a suppressor of endogenous cortisol production were intraperitoneally injected with cortisol (10 mg/Kg). We also included a treatment with mifepristone (GR antagonist) and eplerenone (MR antagonist) in the presence or absence of cortisol. cDNA libraries were constructed from the skeletal muscle of rainbow trout groups: vehicle, cortisol, mifepristone, eplerenone, mifepristone/cortisol and eplerenone/cortisol. RNA-seq analysis revealed that 135 and 68 transcripts were differentially expressed mediated by GR and MR, respectively. In cortisol vs mifepristone/cortisol group, biological processes (BP) were significantly enriched in inflammatory response, ion transmembrane transport, proteolysis, among others. In cortisol vs eplerenone/cortisol group, BP were significantly enriched in muscle contraction, and regulation of cell cycle. To validate these observations, we performed in vitro experiments using rainbow trout myotubes. In myotubes treated with cortisol, we found increased expression of cxcr2, c3, and clca3p mediated by GR, associated with inflammatory response, proteolysis, and ion transmembrane transport, respectively. Contrastingly, MR modulated the expression of myh2 and gadd45g mainly associated with muscle contraction and regulation of cell cycle, respectively. These results suggest that GR and MR have a differential participation in the physiological response to stress in teleost skeletal muscle.